东南极格罗夫山地区冰碛石碎石带中高压麻粒岩和正片麻岩的锆石年代学研究及其构造意义 - 王伟; 刘晓春; 赵越; 郑光高; 陈龙耀 (极地研究, 2016)
东南极的格罗夫山是普里兹造山带向南极内陆的延伸部分。对格罗夫山不同碎石带中收集的高压麻粒岩和正片麻岩进行锆石 U-Pb 年代学研究。四个高压麻粒岩的锆石多数为变质新生锆石，仅少数保留有继承核，其年龄为2633—2502 Ma。在变质锆石中获得～570 Ma 和～555—545 Ma 两个阶段变质年龄，锆石微量元素特征显示为重稀土亏损，结合前人研究结果，推测这两阶段年龄分别代表了变质作用过程中的进变质和高压峰期变质年龄。两个正片麻岩的锆石普遍发育核-边结构，由一个发育振荡环带的岩浆核和均匀无环带的变质边组成。正片麻岩的原岩年龄存在差异，在样品 GR14-3-4的锆石核部获得了1060±40 Ma 的上交点年龄，其原岩可能来自格罗夫山东南部的冰下高地，而在样品 GR14-5-4的锆石核部获得的原岩年龄为917±4 Ma，与格罗夫山基岩中的基性麻粒岩和正片麻岩的原岩年龄一致。在锆石边部获得的变质年龄较为一致，为～530 Ma，与以前在高压麻粒岩中获得的退变质年龄相当。本次研究确认了高压麻粒岩在格罗夫山地区不同碎石带中分布的广泛性，表明其可能普遍存在于格罗夫山冰下高地之中。同时也进一步证明格罗夫山冰下高地并没有受到格林维尔期构造热事件的影响，而是只经历了泛非期的单相变质构造旋回。 High-pressure granulites and orthogneisses from glacial moraines in the Grove Mountains,East Antarctica, were collected for zircon U-Pb isotope analysis.The zircon grains from four high-pressure granulites were mostly of metamorphic origin.However,some contained an inherited core aged 2633—2502 Ma.The metamorphic zircons showed two age stages (~570 Ma and ~555—545 Ma representing the earlier prograde and peak HP metamor-phism ages,respectively)and displayed flat HREE patterns in the chondrite-normalized REE diagram.The zircon grains from two orthogneisses typically showed a magmatic core with oscillatory zoning and a metamorphic rim with-out zoning.Different protolith ages were obtained from zircon cores of these two orthogneisses.An upper intercept age of 1 060 ±40 Ma was obtained from the cores of zircon in one sample,suggesting that its protolith came from the subglacial highlands in the southeast Grove Mountains.Analytical spots from another sample yielded a protolith age of 91 7 ±4 Ma,consistent with the protolith ages obtained for orthogneisses and mafic granulites that crop out in the Grove Mountains.The analytical spots from zircon rims from the two orthogneisses yielded similar metamorphic ages of ~530 Ma,in agreement with the time of retrograde metamorphism of high-pressure granulites reported previous-ly.High-pressure granulites were common in glacial moraines from the Grove Mountains,reflecting their wide-spread occurrence in the subglacial highlands.Moreover,U-Pb zircon dating confirmed that the subglacial high-lands of the Grove Mountains underwent a single Pan-African metamorphic cycle,but there was no evidence of a Grenville-age metamorphic event. 国家海洋局“南北极环境综合考察与评估”专项; 国家自然科学基金项目; 国土资源大调查项目 中国科技核心期刊(ISTIC) 2 159-180 28